Functional and structural insight into lignocellulosic fibers for high-areal-capacity lithium–sulfur batteries. Issue 34 (27th July 2021) - Yun, Jong Hyuk; Kim, Joo-Hyung; Ragupathy, Pitchai; Kim, Dong Jun; Kim, Do Kyung
Abstract : A novel way of absorbing sulfur species by a vascular system of lignocellulosic fibers and hollow VO2 achieved ultrahigh areal capacity, and the extraordinary adsorption behavior was characterized by operando Raman spectroscopy. Abstract : Hemp-fibers have a long history as a source of making paper, ropes, and canvas. Recently, due to their superior mechanical strength with biodegradability, hemp-fibers are resurfacing as an environmentally friendly engineering material. Meanwhile, lithium–sulfur batteries are receiving substantial attention for the next-generation rechargeable batteries, owing to their high energy density combined with the natural abundance of sulfur. Despite these advantages, sulfur active materials still encompass a number of challenges for practical applications, such as intrinsically low electrical conductivity, dissolution in the electrolyte and limited areal loading. By utilizing hemp-fibers as a scaffold for the sulfur active material, herein we report the fabrication of a hybrid porous carbon architecture that mimics the resource acquisition and transport system of vascular plants. The hemp fiber-derived hybrid electrodes show an exceptionally high sulfur loading of 15.36 mg cm −2 and display a high areal capacity of 14.8 mA h cm −2 at 0.1C current rate. We also demonstrate the feasibility of the practical application by fabricating large-area pouch-cells. Furthermore, our operando Raman and X-ray photoelectron spectroscopy studies have revealed the chemisorption mechanism of the hemp hybrid electrode with lithium polysulfide, which enables long cycle life.